2005
DOI: 10.1111/j.0013-0133.2005.00972.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of a Mother’s Return to Work Decision on Child Development in the UK

Abstract: The last 20 years has seen a huge increase in employment among mothers in the first year after giving birth in the UK. We examine whether early maternal employment has an adverse effect on child outcomes. We analyse rich data from a cohort of children born in the UK in the early 1990s and examine the impact of early maternal employment on three outcome variables measuring child cognitive development between four and seven years of age. We also explore whether the effect varies with the mother's educational att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
170
0
9

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 182 publications
(185 citation statements)
references
References 19 publications
6
170
0
9
Order By: Relevance
“…The Avon Longitudinal Survey of Parents and Children (ALSPAC) is a longitudinal study of around 12,000 children born in the Avon area in the early 1990s (Golding et al 2001;Gregg et al 2005). Mothers were recruited into the sample at the point at which they first reported their pregnancy to their doctors.…”
Section: Data and Descriptive Statisticsmentioning
confidence: 99%
“…The Avon Longitudinal Survey of Parents and Children (ALSPAC) is a longitudinal study of around 12,000 children born in the Avon area in the early 1990s (Golding et al 2001;Gregg et al 2005). Mothers were recruited into the sample at the point at which they first reported their pregnancy to their doctors.…”
Section: Data and Descriptive Statisticsmentioning
confidence: 99%
“…Following this period, it is crucial for the mother's return to the workforce and the child's continued healthy development to ensure that high-quality and affordable child care is available. Several studies have shown that parttime employment and employment after age one do not seem to hamper child development when the right child care is available (see, for example, Waldfogel 2004;Averett et al 2005;Gregg et al 2005;Berger et al 2005;and Brooks-Gunn et al 2010). …”
Section: Resultsmentioning
confidence: 99%
“…Given that the quality of the home environment relative to the quality of child care affects whether usage of child care affects a child's development positively or negatively, the redistributional impact of child care policies on child care use is important. Gregg et al (2005) show that there is some evidence that the negative impact of full-time child care in the first 18 months of a child's life is larger for children of higher educated women and smaller for children of single mothers. For part-time child care, no negative effects are found.…”
Section: Child Care Subsidiesmentioning
confidence: 92%
See 2 more Smart Citations